Mobile Apps for Boarding House Recommendation - Effendy, Faried; Kartono, Kartono; Herawatie, Dyah (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This research aims to build a boarding house recommender system based on the Fuzzy TOPSIS method. This application can be utilized by the student community to discover a suitable boarding house. This research uses the classic life cycle (waterfall) as a software development model. The waterfall model consists of 5 stages, namely, communication, planning, modeling, construction, and deployment. In this study, we focus on the construction and deployment stage. To test and assess the system, we use a questionnaire filled by the respondents. Two arrangements of surveys created, one for the students and another for mobile application experts. We use ISO 9126 as a base to assess the system in terms of functionality, usability, content, reliability, and performance. As a result, these mobile apps graded 3.54 and categorized as an excellent system. This system is well-honorable and acknowledged by the student community, which gives a superior, simple method for promoting and reliable tool for finding appropriate boarding houses. The users recommend adding some features such as boarding communities, ratings, reviews so users can communicate with each other and increase the effectiveness and functionality of the application.